Appraisal of Availability and Accessibility to Mortgage Finance for Sustainable Housing Delivery in Nigeria - Atamewan Eugene Ehimatie; Eyo Eyo-Ita Effiom; Effanga Maureen Effanga (European Scientific Journal, ESJ, 2017)
The success of any sustainable housing delivery system depends on a wide range of factors which includes availability and accessibility to mortgage finance. The paper appraised the availability and accessibility to mortgage finance towards sustainable housing delivery system in Nigeria. Methodology of study involved the use of questionnaires to collect information from respondents. Questionnaires were distributed to 320 staff of Cross River University of Technology, Calabar from a population of 1042 staff representing 30.7%.. In addition, fifteen respondents purposely selected were orally interviewed. The data collected were analyzed using simple statistics, percentages and content analysis respectively. The secondary data involved available research data, official documents and data obtained from literature, books and journals. Findings reveal that the key challenge of accessing housing finance in Nigeria is affordability challenge. These include 10% - 30% equity contribution, maximum tenures of only 10-25 years, high interest rate of 22% and the non-availability of long-term funding for housing development The paper opined that availability and accessibility to adequate mortgage financing will stimulate sustainable housing delivery process in Nigeria. Finally, strategies for promoting accessibility to housing financing for sustainable housing delivery is suggested in this paper.